Synthesis and transdermal permeation-enhancing activity of carbonate and carbamate analogs of Transkarbam 12 - Holas, Tomás; Vávrová, Katerina; Síma, Martin; Klimentová, Jana; Hrabálek, Alexandr (Bioorganic & medicinal chemistry, 2006)
Transkarbam 12 (5-(dodecyloxycarbonyl)pentylammonium-5-(dodecyloxycarbonyl)pentylcarbamate, T12) is a highly effective skin permeation enhancer. In this study, ester groups in the molecule of T12 were replaced by carbonate and carbamate ones, respectively. The in vitro permeation-enhancing activities were evaluated using porcine skin and compared with those of T12 and previously prepared series of amide, ketone, and alkyl analogs. According to the activities and behavior of the compounds in donor samples, ester group is essential for the activity of T12; its replacement not only decreases the enhancing potency, but is likely to change the mechanism of action.
Keywords: Skin Absorption; Carbamates; karbamáty; Permeability; Swine; Animals; prasata; Esters; zvířata; estery; adjuvancia farmaceutická; vztahy mezi strukturou a aktivitou; Adjuvants, Pharmaceutic; Carbonates; Structure-Activity Relationship; permeabilita; kožní absorpce; uhličitany